Multiculturalidad y pluralismo jurídico: Nuevas perspectivas para la construcción del discurso sobre los Derechos Humanos - Bonet de Viola, Ana María (2018)
This paper addresses the issue of the validity and adaptation of classical-liberal discourses on Human Rights in the multicultural context of the global community. A genealogical approach is methodologically introduced, which, from the crisis of the classical theory on Human Rights founded on the logic of identity, aims to trace different discursive alternatives that are still in development, towards a pluralistic re-construction of the system of Human Rights. This itinerary will include an approach to the crisis of the universalistic, secular and liberal postulates, which constitute the main critical axes that shape the current debate on the subject. It is thus proposed to analyze the process of discursive transformation which defines the legal arena for future development in the field of Human Rights, highlighting the potential of the discourses of differencewhich would help to overcome the crises stemming from the individualistic logic of identity.